Effectiveness of anti-osteoporotic treatment after successful parathyroidectomy for primary hyperparathyroidism: a randomized, double-blind, placebo-controlled trial - Niederle, Martin B. (Langenbecks Arch Surg, 2019)
PURPOSE: After successful surgery for primary hyperparathyroidism, bone mineral density (BMD) does not improve equally in all patients. As no trial has so far aimed to influence normalization of BMD, it was the goal of this investigation to determine whether pharmacological treatment is effective in improving regain of BMD after successful parathyroidectomy in patients with preoperatively diagnosed osteoporosis or osteopenia and to evaluate when treatment may be indicated. METHODS: In this randomized, placebo-controlled, double-blind trial, 52 patients were treated with strontium ranelate 2 g daily + 1000 mg calcium + 800 IU vitamin D (strontium group; SG) or with 1000 mg calcium + 800 IU vitamin D alone (placebo group; PG) for 1 year. The main outcome measures were BMD (lumbar spine, femoral neck, radius) and bone turnover markers. RESULTS: The baseline characteristics were similar in both groups. Absolute BMD (1.007 ± 0.197 vs. 0.897 ± 0.137 g/cm(2); p = 0.024) and both relative (9.94 vs. 3.94%; p < 0.001) and absolute (0.09 ± 0.06 vs. 0.03 ± 0.04 g/cm(2); p < 0.001) changes in lumbar-spine BMD were significantly higher in the SG than in the PG. Compared to baseline, BMD significantly increased in both groups at the lumbar spine (p < 0.001 and p = 0.001, respectively) and femoral neck (both p < 0.001), whereas radius BMD only changed significantly in the SG. However, the proportion of patients with osteoporosis/osteopenia significantly declined only at the lumbar spine in the SG (from 69.0 to 37.9%; p = 0.034), whereas no decrease was found in the PG. No severe adverse events occurred. CONCLUSIONS: Postoperative anti-osteoporotic treatment can positively influence regain of BMD mainly in the lumbar spine and should be considered. Without treatment, most patients and especially those with low preoperative markers of bone turnover remained osteoporotic/osteopenic 1 year after surgery. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00423-019-01815-9) contains supplementary material, which is available to authorized users.